52 - BEHAVIORAL STUDY OF NEWLY TRAINED PROFESSIONALS IN PHYSICAL EDUCATION (Fiep Bulletin - online, 2021)
The Physical Education professional is seen as an example when it comes to training and healthy living. The research aims to assess the level of training of Physical Education Professionals after graduation. It is a field research, with a qualitative and quantitative approach. Thirty recently graduated physical education professionals from the city of Patos PB participated in the study. A semi-structured questionnaire with objective questions was used, whose data were analyzed and computed in a quantitative way, using Microsoft Excel spreadsheets. The sociodemographic results pointed to 43.48% females and 56.52 males, where 69.57% are single, 21.74% married, 4.35% divorced and 4.35% widowed, 56.52% are graduated and 43.48% are specialists and 8.7% are from 6 months to 1 year old and 91.3 are more than 1 year old, regarding postgraduate behavior regarding training, there was an overall average of 78.5% in statement that they did their practices and knew how to deal with them. It is concluded that these professionals are duly concerned with their post-course attitudes, noting that their permanence in the job market, their own existence as a professional, may be linked to their physical shape, aesthetics and especially support for the day to day with health.